Analysis of Students' Errors in Solving Mathematics Story Problems in View of Learning Styles in Class VII Students of SMP Negeri 13 Mataram Academic Year 2023/2024 - Rosmala Dewi, Lale Amrini; Kurniati, Nani; Lu’luilmaknun, Ulfa; Subarinah, Sri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to describe the level of tendency and causes of students’ errors in solving mathematic story problems. Error analysis was carried out based on the Polya's procedure reviewed from the students' learning styles. This type of research is descriptive qualitative. The sampling technique used purposive sampling and consideration from the mathematics teacher so that class VII H of SMP Negeri 13 Mataram was obtained as the research subject. The sample used was 29 students. Data collection techniques using learning style questionnaires, test questions, and interviews. Data analysis techniques are data collection, data reduction, data presentation, and conclusion drawing. Based on the results of data analysis obtained from test results and interviews, it can be concluded that, students of visual learning styles tend to make mistakes at the plans implementing stage with an error rate of 63% including in the high category and the recheck stage with an error rate of 86% including in the very high category. Students of auditorial learning styles tend to make mistakes at the recheck stage with an error rate of 58% including in the medium category. Students of kinesthetic learning styles tend to make mistakes at the recheck stage with an error rate of 44% including in the low category. The causes of these errors are because 1) students are less to understand the problem, 2) less careful in doing calculations, 3) not used to writing conclusions because students used the results from the previous stage as conclusions.